(3eNJUQ cJGH GdJaGMIs
(3ChdgG (B:s
(3PcQ Cf SbQGW GdajdSha deG MVQJg GdhaGI ELJeY Edjg CUMGHg aQChG ef YdGeGJ GdehJ eG jFShG Hg ef MjGJg s
(3BNQgG (B:s
(3bGd GdMcje EPG cGfJ GdadSaI gi NjQ GdOfjG hKhGHgG gh NjQ GdBNQI bGd heG GdPi LYd MSfGJ GdYGeI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B9s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI LjOI s
Keywords: (3GdadSaI hGdefWbs